Acupuncture and massage: aid in the treatment of patients with hypertension and diabetes in Ejido Cuitláhuac Tacotalpa - Cornelio Montejo, Gustavo Alonso (2016)
Introduction.Nursing has highlighted the inclusion of traditional and alternative medicine as a discipline to prevent, diagnose, treat and rehabilitate the patient with acupuncture and massage techniques. In the WHO Global Health magazine lists diseases that can be treated with this medicine, reducing the impact of diseases that are at the top of morbidity and mortality in Mexico. Objective. Know if acupuncture and massage are alternative treatments aids in hypertension and DM2 users Cuitláhuac health center, Tacotalpa, Tab. Method.Quantitative, transversal, quasi-experimental, in 28 patients with type 2 diabetes and hypertension, with measurements before and after alternative treatment study. Result. With alternative treatment, blood glucose levels dropped from 131 to 124 mg and blood pressure of 140/79 to 123/83 mmHg (p ≤ 0.05). Conclusion. Acupuncture and massage shown to be ancillary to treat chronic diseases, do not have more specific results in Mexico's indigenous population and studies are needed with more robust designs for their effectiveness